Strategi Dakwah Pondok Pesantren Nadwa Dalam Meningkatkan Kualitas Spiritual Qoutient Santri - Parlin Saputra Pasaribu; Faridah Faridah (Universitas Cokroaminoto Yogyakarta, 2026)
This study aims to determine the da'wah strategies implemented by Nadwa Islamic Boarding School in improving the spiritual quotient (SQ) of students. The research uses a qualitative case study approach through in-depth interviews with the boarding school leadership, as well as direct observation of da'wah activities and documentation of the boarding school program. The results indicate that Nadwa Islamic Boarding School implements six main da'wah strategies in the spiritual development of students: Tabligh Persatuan IPN, Yasinan activities and discipline enforcement, additional religious studies after Isha prayer, the formation of a Student Council, the obligation to live in the dormitory for students in grades 4–7, and Da'wah Safari. All of these strategies are designed to instill Islamic values, train responsibility, discipline, and leadership. These strategies not only have an impact on increasing students' religiosity but also have an applicable spiritual quotient in life.